Model charged cylindrical nanopore in a colloidal dispersion: charge reversal, overcharging and double overcharging - González-Tovar, E.; Lozada-Cassou, M. (Condensed Matter Physics, 2017)
Using the hypernetted-chain/mean spherical approximation (HNC/MSA) integral equations we study the electrical double layer inside and outside a model charged cylindrical vesicle (nanopore) immersed into a primitive model macroions solution, so that the macroions are only present outside the nanopore, i.e., the vesicle wall is impermeable only to the external macroions. We calculate the ionic and local linear charge density profiles inside and outside the vesicle, and find that the correlation between the inside and outside ionic distributions causes the phenomena of overcharging (also referred to as surface charge amplification) and/or charge reversal. This is the first time overcharging is predicted in an electrical double layer of cylindrical geometry. We also report the new phenomenon of double overcharging. The present results can be of consequence for relevant systems in physical-chemistry, energy storage and biology, e.g., nanofilters, capacitors and cell membranes.